Darwin and the survival of the fittest in modern interventional cardiology. Issue 8 (31st January 2006) - Bhatia, V K; Di Mario, C
Abstract : The diabetic patient requires a full armamentarium of proven and developing treatments in order to minimise periprocedural risk as well as improve long term outcome